Seismic Noise Analysis of Four Broadband Seismic Stations in Central Part of Iraq Using Probabilistic Power Spectral Density (PPSD) - Qusay, Taif; Abd, Najah (Iraqi Journal of Science, 2026)
Seismic noise analysis is crucial to enhance the reliability of earthquake monitoring networks. Therefore, in this paper, we investigated the ambient seismic noise at four seismic stations in central Iraq, namely Karbala (KAR2), Kut (KUT1), Diyala (DYL1), and Baghdad (BGD1) over a period of one year, by analysing the seismic noise using power spectral density (PSD) and probability density function (PDF) techniques and then comparing the analysis results with Peterson’s models. Our results indicate that most of the stations are within the acceptable noise levels according to Peterson’s model. However, the Karbala (KAR2) station consistently exceeds the New High Noise Model (NHNM) standards over the long periods range. A new station was installed in Karbala, and its noise analysis was calculated, but the results were similar to those of the old station. Therefore, the station location is not ideal for earthquake monitoring and should be moved to a different location.